RESTORATIVE JUSTICE IN THE NEW CRIMINAL CODE: A LITERATURE REVIEW ANALYSING THE SHIFT IN THE PARADIGM OF PUNISHMENT FROM RETRIBUTIVE TO REHABILITATIVE IN INDONESIA - Gunawan Widjaja (JOURNAL OF LAW AND NATION, 2026)
The New Criminal Code, enacted through Law No. 1 of 2023, marks a renewal of national criminal law by positioning punishment no longer merely as retribution, but also as a means of prevention, rehabilitation of offenders, conflict resolution, and the restoration of balance between offenders, victims and society. Within this framework, restorative justice has gained an increasingly important position as an approach that reflects the shift in the paradigm of punishment from retributive to rehabilitative and restorative in Indonesia. This study aims to analyse the implementation of restorative justice in the New Criminal Code and to examine the accompanying shift in the paradigm of punishment through a literature review approach. The method used is a literature review. The findings indicate that the New Criminal Code accommodates a more humanistic approach to punishment through an emphasis on victim restoration, the social reintegration of offenders, the use of alternative sanctions, and the restriction of imprisonment to a last resort. Furthermore, the implementation of restorative justice in practice still requires harmonisation of regulations among law enforcement agencies, strengthening of institutional capacity, and a common understanding among officials to prevent disparities in application. Thus, restorative justice in the New Criminal Code can be understood as part of the transformation of Indonesia’s penal system towards a model that is more rehabilitative, corrective, and responsive to the needs for substantive justice in society.